Rancang Bangun Pembangkit Listrik Tenaga Sampah (PLTSa) Berbasis Bioteknologi Lingkungan: Rancang Bangun Pembangkit Listrik Tenaga Sampah (PLTSa) Berbasis Bioteknologi Lingkungan - Hasyim Suyuti Amin Muzzekki (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2021)
The need for electrical energy is very high, especially in Indonesia, until now it still uses fossil fuels which cannot be renewed, therefore it is necessary to have alternative technologies that can be renewed such as waste power plants, their existence is very much found considering the amount of waste in Indonesia reaches up to 64 million tonnes annually. By using environmental biotechnology, it can be an environmentally friendly source of energy. The results of biogas processing using a 100L tank can produce 23846.26 kcal so that it can produce 27.66 kWh / day. If applied on a large scale at Tps Labang District, Bangkalan Regency, which produces 60 tons of waste every day, 17 July 2020 by taking 50% to 30,000 kg of organic waste every day with a calorific value of 1135.05 kcal. Then the thermal energy obtained is 34,051,500kcal / day. To find the power capacity generated according to the equation, the number (kcal) x 0.00116 (kWh / kcal) = 39.499.74 kWh / day, per day divided by the number of hours that is 24. Then the power capacity of the generator is 1,645.82 kW.